Polyarylene sulfide film for electrolyte membrane reinforcement, film roll, film for electrolyte membrane reinforcement, electrolyte membrane reinforcement member, fuel cell, and water electrolytic apparatus

A polyarylene sulfide film with tailored properties addresses the issue of inadequate dimensional control in fuel cell bonding processes, enhancing processing size control and planarity during roll-to-roll processing.

JP2025058956APending Publication Date: 2025-04-09TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024160692
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-18
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The dimensional control of the bonding process for fuel cells using polyarylene sulfide films as electrolyte membrane reinforcements is inadequate due to tension and heat during transport.

Method used

A polyarylene sulfide film with specific heat shrinkage rates, tear strength ratios, surface free energy, Young's modulus, and surface roughness is developed to enhance processing size control and planarity during roll-to-roll processing.

Benefits of technology

The film provides excellent processing size control and planarity, reducing size deviations and improving the productivity of fuel cell assembly by maintaining dimensional stability under heat and tension.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058956000001_ABST
    Figure 2025058956000001_ABST
Patent Text Reader

Abstract

To provide a polyarylene sulfide film which is excellent in dimensional control of processing.SOLUTION: A polyarylene sulfide film for electrolyte membrane reinforcement contains a polyarylene sulfide (PAS)-based resin as a main component, wherein as for a thermal shrinkage when being treated at a temperature of 125°C for 30 minutes, a longitudinal direction SMD is 0.10% or more and 1.20% or less, and a width direction STD is -0.50% or more and -0.01% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyarylene sulfide film and a film roll for reinforcing an electrolyte membrane. [Background technology]

[0002] In recent years, the trend toward carbon neutrality has led to the development of hydrogen-powered fuel cells and water electrolysis equipment for hydrogen generation. Among these, polymer electrolyte fuel cells have a relatively low reaction temperature and high energy density, and are therefore expected to find a wide range of applications as power generation equipment for relatively small-scale distributed power generation facilities and mobile vehicles such as automobiles and ships.

[0003] The electrolyte membrane currently being considered for use in solid polymer fuel cells is a proton-conductive ion exchange membrane, and in particular, a cation exchange membrane made of perfluorosulfonic acid containing sulfonic acid groups, such as Nafion (registered trademark), is being widely considered.

[0004] Fuel cells have a layered structure in which multiple cells are stacked on top of each other. The electrolyte membrane, one of the components of the cell, is difficult to handle because it lacks stiffness. When joining the individual electrodes or when assembling multiple single cells into a stack, wrinkles often form around the edges. This means that the electrolyte membrane has the lowest mechanical strength of all the components of the stack, posing a problem in terms of productivity.

[0005] Therefore, Patent Document 1 describes the provision of a reinforcing material around the periphery of the fuel cell, which mechanically reinforces the electrolyte membrane and is hermetically bonded to the electrolyte membrane to prevent leakage of fuel gas and oxidant gas from the boundary surface with the electrolyte membrane. It also describes that the reinforcing material should preferably have the required mechanical strength, corrosion resistance, etc. even at operating temperatures, and that polyethylene naphthalate is used for the reinforcing material.

[0006] Polyarylene sulfide has excellent properties such as heat resistance, hydrolysis resistance, flame retardancy, rigidity, chemical resistance, electrical insulation, and low moisture absorption, and is particularly suitable for use in electrical and electronic equipment, machine parts, and automobile parts. In the field of fuel cells, materials with high hydrolysis resistance and durability are required, and polyarylene sulfide films, such as polyphenylene sulfide (hereinafter sometimes abbreviated as PPS), are being applied to electrolyte membrane reinforcing members by taking advantage of their high hydrolysis resistance.

[0007] So far, a technology for reinforcing members for solid electrolyte membranes in which the metal element-containing components of PPS resin have been reduced has been disclosed (Patent Document 2). In addition, a technology for reinforcing materials for electrolyte membranes that are given flexibility by laminating with fluororesin has been disclosed (Patent Document 3). In addition, a technology for reducing the thermal shrinkage of PPS films from the viewpoint of dimensional stability has been disclosed (Patent Document 4). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2007-103170 A [Patent Document 2] JP 2016-219136 A [Patent Document 3] JP 2013-110048 A [Patent Document 4] International Publication No. 2021 / 045076 Summary of the Invention [Problem to be solved by the invention]

[0009] In recent years, with the spread of fuel cells, developments are underway to increase the speed and efficiency of lamination of membrane electrode assemblies (MEAs) including electrolyte membrane reinforcing members and electrolyte membranes by processing them in long strips using roll-to-roll processing. With roll-to-roll processing, it is important to control deformation due to tension and temperature during transportation. However, it has been found that even with the technology described in the above patent document, there is an issue of insufficient dimensional control of lamination processing due to the addition of tension and deformation due to heat during transportation.

[0010] An object of the present invention is to solve the above-mentioned problems, that is, to provide a polyarylene sulfide for reinforcing an electrolyte membrane, which has excellent dimensional controllability. [Means for solving the problem]

[0011] A preferred embodiment of the present invention is as follows. (1) The thermal shrinkage rate (longitudinal S) of a material mainly composed of polyarylene sulfide (PAS) resin when heated at 125°C for 30 minutes MD、 Width direction S TD ) in the longitudinal direction S MD is 0.10% or more and 1.20% or less, and the width direction S TD A polyarylene sulfide film for reinforcing an electrolyte membrane, having a viscosity of -0.50% or more and -0.01% or less. (2) Longitudinal tear strength (H MD ) and transverse tear strength (H TD ) satisfies the following formula (1): 1.01≦H TD / H MD <= 2.00 (3) The polyarylene sulfide film for reinforcing an electrolyte membrane according to (1) or (2), having a surface free energy measured on at least one surface of 50 mN / m or more. (4) Thermal shrinkage rate S in the longitudinal direction at 125°C for 30 minutes MD and the thermal shrinkage rate S in the width direction TDThe polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (3), which satisfies the following formula: -0.85≦5.5S MD +12S TD ≦0.85 (5) Thermal shrinkage rate (longitudinal S) when heated at 125°C for 30 minutes MD、 Width direction S TD ) in the longitudinal direction S MD is 0.20% or more and 1.00% or less, and the width direction S TD The polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (4), wherein the elastic modulus is −0.40% or more and −0.10% or less. (6) The polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (5), having a Young's modulus in both the longitudinal and transverse directions of 3.5 GPa or more and 4.5 GPa or less. (7) The polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (6), wherein at least one surface has a surface roughness (SRa) of 20 nm or more and 100 nm or less. (8) The polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (7), in which a differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 5.2 in a molecular weight distribution curve measured by gel permeation chromatography (hereinafter referred to as GPC) is 0.10 or more and 0.50 or less. (Measurement method) A differential molecular weight distribution curve is obtained according to JIS K7252 (2016). Specifically, 5 mL of 1-chloronaphthalene (1-CN) is added to 5 mg of sample, and the mixture is gently stirred at 210-220 °C for 20 minutes to visually confirm that the sample is dissolved. Then, the mixture is filtered using a 0.5 μm filter. The measurement is performed under the conditions shown below to obtain a GPC curve. The obtained GPC curve is converted using a molecular weight calibration curve created by approximating the relationship between the logarithm of the molecular weight of polystyrene and the elution time with a cubic equation to calculate a differential molecular weight distribution curve. Note that the molecular weight is a relative value based on the polystyrene standard, and the differential molecular weight distribution curve is drawn by plotting the differential molecular weight and its weight fraction, and normalized so that the peak area is 1. From the obtained differential molecular weight distribution curve, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 5.2 is read. Equipment: High temperature GPC equipment (equipment No. GPC-H-2, PL-GPC220 manufactured by Polymer Laboratories) Detector: Refractive index detector (RI) Data interval: Every 0.5 seconds Column: Shodex UT-G (guard column) PLgel 10m MIXED-B-LS (2 pieces) (8.0mm x 30cm, Polymer Laboratories) Solvent: 1-chloronaphthalene Flow rate: 0.7mL / min Column temperature: 210℃ Injection volume: 0.200mL Standard sample: Tosoh monodisperse polystyrene (9) The polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (8), wherein in a molecular weight distribution curve measured by a GPC method, a differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 4.0 is 0.10 or more and 0.40 or less. (Measurement method) A differential molecular weight distribution curve is obtained according to JIS K7252 (2016). Specifically, 5 mL of 1-chloronaphthalene (1-CN) is added to 5 mg of sample, and the mixture is gently stirred at 210-220 °C for 20 minutes to visually confirm that the sample is dissolved. Then, the mixture is filtered using a 0.5 μm filter. The measurement is performed under the conditions shown below to obtain a GPC curve. The obtained GPC curve is converted using a molecular weight calibration curve created by approximating the relationship between the logarithm of the molecular weight of polystyrene and the elution time with a cubic equation to calculate a differential molecular weight distribution curve. Note that the molecular weight is a relative value based on the polystyrene standard, and the differential molecular weight distribution curve is drawn by plotting the differential molecular weight and its weight fraction, and normalized so that the peak area is 1. From the obtained differential molecular weight distribution curve, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 4.0 is read. Equipment: High temperature GPC equipment (equipment No. GPC-H-2, PL-GPC220 manufactured by Polymer Laboratories) Detector: Refractive index detector (RI) Data interval: Every 0.5 seconds Column: Shodex UT-G (guard column) PLgel 10m MIXED-B-LS (2 pieces) (8.0mm x 30cm, Polymer Laboratories) Solvent: 1-chloronaphthalene Flow rate: 0.7mL / min Column temperature: 210℃ Injection volume: 0.200mL Standard sample: Tosoh monodisperse polystyrene (10) A polyarylene sulfide film roll for reinforcing an electrolyte membrane, obtained by winding up any one of the films (1) to (9). (11) A polyarylene sulfide film for reinforcing an electrolyte membrane according to any one of (1) to (9), which is laminated with an electrolyte membrane and / or a membrane electrode assembly by roll-to-roll bonding. (12) A film made of a thermoplastic resin, the heat shrinkage rate (longitudinal S) when heat-treated at a temperature of 125°C for 30 minutes MD、 Width direction S TD ) in the longitudinal direction S MDis 0.10% or more and 1.20% or less, and the width direction S TD The electrolyte membrane reinforcing film has a refractive index of -0.50% or more and -0.01% or less. (13) An electrolyte membrane reinforcing member using the film according to any one of (1) to (9) and (12). (14) A fuel cell having the electrolyte membrane reinforcing member according to (13). (15) A water electrolysis device having the electrolyte membrane reinforcing member according to (13). Effect of the Invention

[0012] INDUSTRIAL APPLICABILITY The present invention provides a polyarylene sulfide film for reinforcing an electrolyte membrane, which has excellent dimensional controllability, and can be suitably used as an electrolyte membrane reinforcing member for fuel cells and water electrolysis devices, which require high degree of dimensional control and flatness. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram showing an example of a polyarylene sulfide film roll for reinforcing an electrolyte membrane having openings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described. A preferred embodiment of the present invention is a film made of a polyarylene sulfide (hereinafter, PAS) resin as a main component, and has a thermal shrinkage rate (longitudinal shrinkage S) of 125° C. for 30 minutes. MD、 Width direction S TD ) in the longitudinal direction S MD is 0.10% or more and 1.20% or less, and the width direction S TD The present invention relates to a polyarylene sulfide film for reinforcing an electrolyte membrane, the polyarylene sulfide film having a viscosity of -0.50% or more and -0.01% or less. By adopting this embodiment, it is possible to obtain a polyarylene sulfide film for reinforcing an electrolyte membrane, which has excellent dimensional controllability.

[0015] In the present invention, the term "mainly composed of PAS resin" means that the PAS resin is contained in an amount of 90% by mass or more. More preferably, the PAS resin is contained in an amount of 95% by mass or more. If the PAS resin content is less than 90% by mass, the heat resistance, hydrolysis resistance, chemical resistance, electrical properties, and mechanical properties, which are characteristics of PAS films, may be impaired.

[0016] It is possible to contain a thermoplastic resin other than a PAS-based resin so long as the content is less than 10% by mass, which is within a range that does not impair the effects of the present invention. Examples of such a resin include various polymers such as polyamide, polyetherimide, polyethersulfone, polysulfone, polyphenylene ether, polyphenylsulfone, polyester, polyarylate, polyamideimide, polycarbonate, polyolefin, polyetheretherketone, and fluororesin, as well as blends containing at least one of these polymers.

[0017] The PAS resin used in the present invention is a copolymer having a repeating unit of -(Ar-S)-, where Ar includes units represented by the following formulae (A) to (K).

[0018] [ka]

[0019] (R1 and R2 are substituents selected from hydrogen, alkyl groups, alkoxy groups, and halogen groups, and R1 and R2 may be the same or different.)

[0020] As the repeating unit, a p-arylene sulfide unit represented by the above formula (A) is preferable, and representative examples thereof include polyphenylene sulfide, polysulfone, polyethersulfone, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, and the like. From the viewpoints of film properties and economic efficiency, a particularly preferable p-arylene sulfide unit is a p-phenylene sulfide unit.

[0021] The PAS resin used in the present invention is preferably composed of p-phenylene sulfide units represented by the following structural formula as the main structural unit, which accounts for 80 mol % to 99.9 mol % of all repeating units. By using the above composition, excellent heat resistance and chemical resistance can be achieved.

[0022] [ka]

[0023] In addition, it can also be copolymerized with a copolymerization unit in an amount of 0.01 mol % or more and 20 mol % or less of the repeating unit. Preferred copolymer units include the following:

[0024] [ka]

[0025] [ka]

[0026] [ka]

[0027] (wherein X represents an alkylene, CO, or SO2 unit.)

[0028] [ka]

[0029] [ka]

[0030] (where R represents an alkyl, nitro, phenylene, or alkoxy group.)

[0031] The mode of copolymerization is not particularly limited, but a random copolymer is preferred.

[0032] In the film of the present invention, "for reinforcing an electrolyte membrane" means that the film is punched into a frame or picture frame shape and has an opening, and is used as an electrolyte membrane reinforcing member that is pasted to the electrolyte membrane. In the frame-shaped electrolyte membrane reinforcing member with an opening, the center where the electrodes are laminated is cut into the shape of the electrode, and the electrolyte membrane reinforcing member is present only in the peripheral portion. The electrolyte membrane reinforcing member can be used by pasting at least one electrolyte membrane reinforcing member to the peripheral portion of the electrolyte membrane. In another preferred embodiment, two electrolyte membrane reinforcing members are used in a stacked manner. Specifically, one embodiment is one in which the peripheral portion of the electrolyte membrane is sandwiched between the electrolyte membrane and one electrolyte membrane reinforcing member is used on each side of the electrolyte membrane. Furthermore, two or more electrolyte membrane reinforcing members may be used in a stacked manner on each side of the electrolyte membrane through the peripheral portion.

[0033] A preferred embodiment of the film of the present invention is a film having a heat shrinkage rate (longitudinal S MD、 Width direction S TD ) in the longitudinal direction S MD is 0.10% or more and 1.20% or less, and the width direction S TD is -0.50% or more and -0.01% or less. In a bonding process such as thermal lamination, the film expands in the longitudinal direction due to temperature and transport tension when transported, while shrinking in the width direction due to Poisson's ratio. Since the electrolyte membrane reinforcing member is a frame-shaped member with the electrode portion punched out, deformation or deviation may occur due to temperature and transport tension when bonding with the electrolyte membrane or MEA. When bonding with the electrolyte membrane or MEA, particularly in roll-to-roll processing, the film of the present invention has a thermal shrinkage rate within the above range, so that deformation due to heat and tension can be suppressed, processing dimensional control can be facilitated, and size deviation after bonding can be reduced. If the thermal shrinkage rate is outside the above range, dimensional control during bonding processing may be difficult. Longitudinal thermal shrinkage S MDis more preferably 0.25% or more, further preferably 0.40% or more, and particularly preferably 0.52% or more. MD is more preferably 1.00% or less, further preferably 0.90% or less, and particularly preferably 0.80% or less. TD is more preferably -0.40% or more, and even more preferably -0.35% or more, and the thermal shrinkage rate S TD is more preferably −0.10% or less, further preferably −0.19% or less, and particularly preferably −0.24% or less. In order to set the heat shrinkage rate of the present invention within the above-mentioned range, it can be controlled by the film formation conditions described later.

[0034] In the present invention, the longitudinal direction refers to the belt-like direction of the film roll, and the film width direction refers to the direction perpendicular to the longitudinal direction, i.e., the direction between both ends of the film roll. On the other hand, when the film is in a cut sheet form and the longitudinal direction cannot be determined, one of the directions is set to 0°, and the thermal shrinkage at a temperature of 125°C is measured while changing the direction in the film plane at 10° intervals from -90°C to 90°C, and the direction with the largest thermal shrinkage is regarded as the film longitudinal direction.

[0035] The film of the present invention has a longitudinal heat shrinkage ratio S of 125°C for 30 minutes. MD and the thermal shrinkage rate S in the width direction TD It is preferable that the following formula (i) is satisfied. Formula (i) -0.85≦5.5S MD +12S TD ≦0.85

[0036] When the heat shrinkage rate is within the range of the above formula, the dimensional change after the film of the present invention is bonded to an electrolyte membrane or MEA can be further reduced. If it is outside the range of the above formula, the balance of the dimensional change is lost, and the processing dimensional control may be deteriorated. In order to make it within the range of the above formula, it can be controlled by the membrane production conditions described later.

[0037] The film of the present invention has a longitudinal tear strength (H MD ) and transverse tear strength (H TD) preferably satisfies the following formula (ii). Formula (ii) 1.01≦H TD / H MD <= 2.00

[0038] When the tear strength ratio is within the above formula, it indicates that the molecular chains are oriented in the longitudinal direction of the conveying tension, particularly in roll-to-roll processing, and the tear strength in the width direction is high. In the bonding process with an electrolyte membrane or MEA, the electrolyte membrane reinforcing polyarylene sulfide film may be punched and conveyed with an opening as shown in FIG. 1, and tearing at the punched end is suppressed, which is preferable because it improves processability. When the tear strength ratio is less than 1.01, the molecular chains are aligned in the width direction, which may be easily avoided by the conveying tension, and the processability may be deteriorated. When the tear strength ratio exceeds 2.00, the molecular chains are aligned extremely in the longitudinal direction, and high orientation proceeds too much, which may deteriorate the film formation stability in the film formation process. The tear strength ratio is more preferably 1.25 or more, even more preferably 1.40 or more, and the tear strength ratio is more preferably 1.90 or less. In order to set the tear strength ratio of the present invention to the above-mentioned range, it can be controlled by the film formation conditions described later.

[0039] The film of the present invention preferably has a surface free energy of 50 mN / m or more measured on at least one surface. If the surface free energy is within the above range, the adhesive strength can be improved when the polyarylene sulfide film of the present invention is used as an electrolyte membrane reinforcing member provided with an adhesive layer. If the surface free energy value is less than 50 mN / m, the wettability of the film is low, and there may be a problem of peeling between the film and the adhesive layer. In addition, when used for a long time, the adhesive strength may be weak and durability may be poor. The surface free energy is more preferably 52 mN / m or more, and even more preferably 55 mN / m or more. The surface free energy can be measured under the conditions described below. In the present invention, a method for setting the surface free energy value within the desired range includes subjecting one or both sides of the film to a corona discharge treatment or a plasma discharge treatment. The discharge treatment may be performed during the film manufacturing process or at a stage after the film is manufactured. However, if a heat treatment such as an annealing treatment is performed after the discharge treatment, the effect of the discharge treatment may be inactivated. The discharge treatments listed here may be performed alone or multiple times.

[0040] The film of the present invention preferably has a Young's modulus of 3.5 GPa or more and 4.5 GPa or less in both the longitudinal direction and the width direction. The Young's modulus may be referred to as the elastic modulus here. When the elastic modulus is within the above range, it indicates that the rigidity can be maintained, and the occurrence of wrinkles and undulations can be suppressed in the entire film even under the conveying tension during processing, and it is preferable because it can suppress the deterioration of flatness due to heat and tension during processing. When the elastic modulus is less than 3.5 GPa, the rigidity is low and the dimensional control during processing may deteriorate, or the flatness due to processing may deteriorate. When the elastic modulus exceeds 4.5 GPa, the molecular chains are extremely aligned and the high orientation proceeds too much, so that the film formation stability in the film formation process may deteriorate. The elastic modulus is preferably 3.7 GPa or more, and the elastic modulus is preferably 4.2 GPa or less. The elastic modulus can be controlled by the stretching ratio among the film formation conditions described later.

[0041] The film of the present invention preferably has a surface roughness (SRa) of at least one surface of 20 nm or more and 100 nm or less. SRa is a parameter of three-dimensional surface roughness, and means the average roughness at the center plane when the surface roughness curve is approximated by a sine curve, and is defined as the center plane average roughness. The center plane average roughness is a three-dimensional extension of the center line average roughness (Ra) of the two-dimensional roughness parameter described in JIS-B0601-1994, and is obtained by dividing the volume of the part surrounded by the surface shape curved surface and the center plane by the measured area. When the center plane is the XY plane, the vertical direction is the Z axis, and the measured surface shape curve is f(x, y), it is defined by the following formula (iii). Here, Lx is the measured length in the X direction, and Ly is the measured length in the Y direction.

[0042]

number

[0043] By setting the SRa within the above range, the film has excellent running properties, and the film can suppress the conveyance deviation during lamination processing, and the film has excellent dimensional change during processing. If the surface roughness (SRa) of the film surface is less than 20 nm, the surface is smooth, so friction during conveyance is large, and there may be many defects due to reduced conveyance properties and scratches during conveyance. If the surface roughness (SRa) of the film surface is more than 100 nm, the surface is uneven and the film may slip easily when rolled, causing a winding deviation. In addition, the film may easily misalign during lamination processing, and the processing dimension control may be poor. The surface roughness (SRa) of the film surface is more preferably 20 nm or more, and even more preferably 30 nm or more. The surface roughness (SRa) of the film surface is more preferably 80 nm or less, and even more preferably 70 nm or less. The surface roughness (SRa) of the film surface can be controlled to be within the above range by the particles and other resins contained in the film described later. The surface roughness (SRa) of the film surface can be evaluated by the method described later.

[0044] In order to control the surface roughness of the film, there is a method of adding inactive particles within a range that does not impair the effects of the present invention. Examples of the inactive particles referred to here include inorganic fillers such as silica, alumina, calcium carbonate, barium carbonate, barium titanate, barium sulfate, calcium silicate, magnesium oxide, titanium oxide, and zinc oxide, and particles of organic polymer compounds that do not melt at 300°C (e.g., cross-linked polystyrene, etc.). By adding inactive particles, the slipperiness of the film can be improved in the film stretching process, the occurrence of wrinkles during the film running between rolls can be suppressed, and the surface unevenness of the film can be maintained even if the temperature of the heat setting following the transverse stretching is increased, so that the surface scratches can be suppressed and the running property can be improved.

[0045] The film of the present invention preferably has a peak in the range of logarithmic molecular weight Log(M) 4.0 to 6.0 in the molecular weight distribution curve measured by gel permeation chromatography described later. In addition, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 5.2 is preferably 0.10 to 0.50. When the differential molecular weight distribution value is within the above range, it indicates that a large amount of molecular chains with high molecular weight are contained, and the molecular chains are more entangled, which can suppress breakage due to tension during lamination processing of an electrolyte membrane or MEA. When the differential molecular weight distribution value is less than 0.10 when the logarithmic molecular weight Log(M) is 5.2, the molecular chains are less entangled, which may deteriorate the processability during lamination processing. In addition, there is less entanglement during stretching, which may prevent stress propagation and make it difficult for the molecular chains to be oriented. If the differential molecular weight distribution value is greater than 0.50 when the logarithmic molecular weight Log(M) is 5.2, the viscosity during melt extrusion will be high due to the high molecular weight component, and the thickness will vary greatly when molded into an electrolyte membrane reinforcing member, resulting in a large thickness unevenness of the electrolyte membrane reinforcing polyarylene sulfide film. From the above viewpoint, the differential molecular weight distribution value is more preferably 0.15 or more when the logarithmic molecular weight Log(M) is 5.2, and even more preferably 0.20 or more. The differential molecular weight distribution value is more preferably 0.45 or less when the logarithmic molecular weight Log(M) is 5.2, and even more preferably 0.40 or less.

[0046] In the polyarylene sulfide film for reinforcing an electrolyte membrane in the present invention, the differential molecular weight distribution value (dw / dLog(M)) is preferably 0.10 or more and 0.40 or less when the logarithmic molecular weight Log(M) is 4.0 in the molecular weight distribution curve measured by the gel permeation chromatography method described later. The differential molecular weight distribution value indicates the content of low molecular weight components, and when the differential molecular weight distribution value is in the above range, it indicates that a certain amount of low molecular weight components remains while reducing the low molecular weight components, and the low molecular weight components function as a lubricant between molecular chains and become soft components, so that burrs and cracks during punching are suppressed and the processability is excellent. When it is less than 0.10, the low molecular weight components become too small, so that burrs and cracks occur during punching, and the processability may deteriorate. When the differential molecular weight distribution value is greater than 0.40 when the logarithmic molecular weight Log(M) is 4.0, the low molecular weight components become more abundant, and the durability may be poor under the temperature and pressure in the usage environment. From the above viewpoints, when the logarithmic molecular weight Log(M) is 4.0, the differential molecular weight distribution is more preferably 0.10 or more, and even more preferably 0.20 or more.When the logarithmic molecular weight Log(M) is 4.0, the differential molecular weight distribution is more preferably 0.35 or less, and even more preferably 0.30 or less.

[0047] The film of the present invention may be either an unstretched film obtained by melt-molding a resin composition mainly composed of a PAS resin into a sheet, or a biaxially stretched film obtained by biaxially stretching and heat treatment, and from the viewpoint of productivity, a biaxially oriented film is preferred. As the method of biaxial stretching, any of the inflation simultaneous biaxial stretching method, the stenter simultaneous biaxial stretching method, and the stenter sequential biaxial stretching method may be used, and among them, the stenter sequential biaxial stretching method is preferably used from the viewpoint of controlling the film formation stability and the dimensional stability of the film.

[0048] A preferred embodiment of the present invention is a polyarylene sulfide film roll for reinforcing an electrolyte membrane, which is obtained by winding a polyarylene sulfide film. The film roll of the present invention preferably has a film width of 200 mm or more. The film may be an intermediate product roll wound immediately after the film is produced, or may be a product roll obtained by slitting the intermediate product roll.

[0049] The film of the present invention may be a single film or a composite film.

[0050] The thickness of the film of the present invention is not particularly limited, but from the viewpoint of film formability, the film thickness is preferably 0.5 μm or more and 300 μm or less. From the viewpoint of handleability, the film thickness is more preferably 10 to 150 μm, and further preferably 20 to 125 μm. The film thickness can be measured with a known micrometer, and the details will be described later.

[0051] The method for producing the film of the present invention will be described using an example of a film production method in which polyphenylene sulfide resin (hereinafter sometimes abbreviated as PPS resin) is used as the polyarylene sulfide resin, but the present invention is not limited to this example.

[0052] Sodium sulfide and p-dichlorobenzene are mixed and reacted under high temperature and pressure in an amide polar solvent such as N-methyl-2-pyrrolidone (NMP). If necessary, it is possible to add copolymerization components such as m-dichlorobenzene and trihalobenzene. Caustic potash or alkali metal carboxylate is added as a polymerization degree regulator and the polymerization reaction is carried out at 230 to 290 ° C. After polymerization, the polymer is cooled, and the polymer is made into a water slurry and filtered through a filter to obtain a wet granular polymer. An amide polar solvent is added to this granular polymer, and the polymer is stirred and washed at a temperature of 30 to 100 ° C., washed several times with ion-exchanged water at 30 to 80 ° C., washed several times with a metal salt aqueous solution such as a calcium acetate aqueous solution, and then dried to obtain a granular polymer of polyphenylene sulfide (PPS granules). This granular polymer is fed into a vented extruder and melt-extruded into a strand shape, cooled with water at a temperature of 25 ° C., and then cut to produce chips to produce PPS pellets.

[0053] The PPS granules obtained as above as the polyarylene sulfide resin are mixed with inorganic particles and / or other thermoplastic resins in an arbitrary ratio to prepare a master batch. The concentration of the inorganic particles and / or other thermoplastic resins in the master batch is preferably 1% by mass to 25% by mass, more preferably 5% by mass to 15% by mass. If it is more than 25% by mass, the dispersibility may deteriorate and the dispersion diameter may become large. If it is less than 1% by mass, it may be diluted and the amount of the master batch used may increase when used, which may be undesirable from the viewpoint of cost. In the present invention, the method of preparing the master batch is preferably a method of making the master batch using a device that applies shear stress, such as a twin-screw extruder. In this case, it is preferable to knead in the kneading section so that the resin temperature ranges from (melting point of PAS resin + 5°C) to (melting point of PAS resin + 80°C), more preferably from (melting point of PAS resin + 10°C) to (melting point of PAS resin + 80°C), and even more preferably from (melting point of PAS resin + 15°C) to (melting point of PAS resin + 70°C). It is also preferable to set the screw rotation speed in the range of 100 rpm to 1500 rpm. By setting the resin temperature and screw rotation speed in the preferred ranges, the dispersion diameter of the dispersed phase can be controlled.

[0054] In the present invention, it is preferable to first mix PPS chips, which have been dried under reduced pressure at 180°C for 3 hours as necessary, with a master batch in a prescribed ratio, supply the mixture to a full-flight single-screw extruder with a melting section set at 300 to 350°C, pass the mixture through a filter, and then extrude the mixture from a T-die type nozzle.Then, the mixture is brought into close contact with a cooling drum having a surface temperature of 20 to 70°C while applying a static charge thereto, and rapidly cooled and solidified, to obtain an unstretched film in a substantially unoriented state.

[0055] Next, the unstretched film obtained above is biaxially stretched by a sequential biaxial stretching machine or a simultaneous biaxial stretching machine in a temperature range equal to or higher than the glass transition point (Tg) of the polyarylene sulfide resin, and then a one-stage or multi-stage heat treatment is performed at a temperature range of 150 to 280°C to obtain a biaxially oriented film. As the stretching method, a sequential biaxial stretching method (a stretching method in which stretching in one direction is combined, such as a method in which stretching in the longitudinal direction is performed after stretching in the transverse direction), a simultaneous biaxial stretching method (a method in which stretching in the longitudinal direction and the transverse direction is performed simultaneously), or a method combining these can be used. Here, a sequential biaxial stretching method in which stretching in the longitudinal direction is performed first and then in the transverse direction is illustrated as an example.

[0056] The unstretched film is heated by a group of heating rolls and stretched in the longitudinal (MD) direction to 3.0 times or more, more preferably 3.3 times or more, even more preferably 3.5 times or more, and particularly preferably 3.8 times or more in one or two or more stages (MD stretching). By setting the MD stretching within the above range and aligning the molecular chains in the longitudinal direction, the heat shrinkage of the present invention can be controlled. There is no particular restriction on the MD stretching ratio, but a preferred range is 5.0 times or less, more preferably 4.8 times or less, and even more preferably 4.5 times or less. If it exceeds this range, the orientation in one direction is too much by MD stretching, and the film formability during stretching in the transverse direction may deteriorate. The stretching temperature is Tg to Tcc (temperature-rising crystallization peak temperature), preferably in the range of (Tg+5) to (Tcc-5) ° C. Then, it is cooled with a group of cooling rolls at 20 to 50 ° C.

[0057] The stretching in the transverse direction (TD direction) following the stretching in the MD direction is carried out, for example, by using a tenter. The film is generally held at both ends by clips and guided to a tenter. Stretching is performed (TD stretching). The stretching temperature is Tg (glass transition temperature of polyarylene sulfide). ) to (Tg+40)°C, and more preferably (Tg+2) to (Tg+30)°C. In the case of PPS, the temperature is in the range of 95°C to 135°C, and more preferably 97°C to 125°C. The stretching ratio is 3.0 to 4.2 times, preferably 3.0 to 4.2 times, from the viewpoint of obtaining a film with good flatness. is preferably in the range of 3.1 to 4.1 times, and more preferably in the range of 3.2 to 4.0 times.

[0058] In this case, the ratio of the MD magnification to the TD magnification (stretching magnification ratio = MD magnification / TD magnification) of the stretching magnification of the film is preferably more than 1.0, more preferably 1.1 or more, and more preferably 1.2 or more, from the viewpoint of aligning the molecular chains in the longitudinal direction and suppressing breakage in the width direction during transport. If the stretching magnification ratio is 1.0 or less, the molecular chains are aligned in the width direction, and may be broken by the tension during transport, resulting in poor processability.

[0059] Next, the stretched film is heat-set under tension (heat setting treatment). The heat setting temperature is either the same temperature throughout the heat treatment zone, one-stage heat setting, or multi-stage heat setting in which heat treatment is performed at different temperatures in the first and second halves of the heat treatment zone. The heat setting temperature is preferably 200°C to the melting point (Tm), and preferably 250 to (Tm-10)°C from the viewpoint of suppressing thermal shrinkage of the film.

[0060] Next, it is preferable to perform a relaxation treatment in the longitudinal direction and / or width direction while holding the heat-set biaxially oriented film with clips. In the present invention, it is preferable to perform the relaxation treatment in the width direction in two or more stages with different temperatures. By performing the relaxation treatment in two or more stages with different temperatures, it is possible to relax the orientation strain at each temperature, and it is a preferable embodiment because the thermal shrinkage rate in the TD direction can be well controlled. The relaxation rate is a ratio value of the difference between the width between the clips before the treatment and the width after the treatment, and for example, a relaxation rate of 2% indicates that when the width before the treatment is 100 mm, it is relaxed by 2% (2 mm) to become 98 mm after the treatment. In the previous stage of relaxation treatment (hereinafter sometimes abbreviated as Rx1), the relaxation rate is preferably 1.0 to 10.0%, more preferably 3.0 to 7.0%. In addition, the temperature during the relaxation treatment (Rx1) is preferably (heat setting temperature -20) ° C or more (heat setting temperature +10 ° C) or less. In the latter relaxation treatment (hereinafter sometimes abbreviated as Rx2), the relaxation rate is preferably 0.1 to 10%, more preferably 3 to 8%. The temperature in the latter relaxation treatment (Rx2) is preferably (heat setting temperature - 80) °C or higher and (heat setting temperature - 10) °C or lower.

[0061] After that, the film is cooled to a temperature of preferably 35°C or less, more preferably 25°C or less, and then the film edges are removed and wound on a core. Furthermore, from the viewpoint of improving thermal dimensional stability, the wound PPS film may be conveyed under tension under a certain temperature condition and annealed. The annealing temperature is more preferably 130°C or more and 190°C or less. If it is 190°C or more, the shrinkage strain is excessively removed during the annealing treatment, resulting in a state in which the molecular chains are largely relaxed. When temperature and tension are applied to the film again in the subsequent process, this may lead to dimensional changes during processing, which may deteriorate the processing dimensional control. If it is less than 130°C, the removal of the strain in the molecular structure by the annealing treatment may be incomplete, which may deteriorate the processing dimensional control. The annealing temperature is preferably 140°C or more and 180°C or less. The conveying tension during annealing is preferably 0.5MPa to 3.0MPa, more preferably 0.8MPa to 2.0MPa. The annealing time is preferably from 1 to 200 seconds, more preferably from 10 to 100 seconds, and further preferably from 10 to 50 seconds. The annealing treatment is carried out while conveying at a speed of 1 to 100 m / min, to obtain the film of the present invention.

[0062] In the present invention, the polyarylene sulfide film or its film roll may be subjected to any processing such as molding, surface treatment, lamination, coating, printing, embossing, and etching, if necessary.

[0063] The film of the present invention is preferably used as an electrolyte membrane reinforcing member. The electrolyte membrane reinforcing member may be bonded to the electrolyte membrane via an adhesive layer, and a known method (e.g., JP-A-2015-2029, JP-A-2022-69952) can be applied to the film of the present invention.

[0064] The cells used in fuel cells and water electrolysis devices have a structure in which a catalyst layer, an electrode substrate, and a separator are laminated in this order on both sides of an electrolyte membrane reinforced with the film of the present invention. Of these, an electrolyte membrane having a catalyst layer laminated on both sides (i.e., a layer structure of catalyst layer / electrolyte membrane / catalyst layer) is called a catalyst-coated electrolyte membrane (CCM), and an electrolyte membrane having a catalyst layer and a gas diffusion substrate laminated in this order on both sides (i.e., a layer structure of gas diffusion substrate / catalyst layer / electrolyte membrane / catalyst layer / gas diffusion substrate) is called a membrane electrode assembly (MEA).

[0065] Common methods for manufacturing a CCM include a coating method in which a catalyst layer paste composition for forming a catalyst layer is applied to the surface of an electrolyte membrane and dried, and a method in which only a catalyst layer is prepared on a substrate and this catalyst layer is transferred to laminate the catalyst layer on the electrolyte membrane (transfer method). The end of the electrolyte membrane in this CCM or MEA is placed on the peripheral edge of the opening of the film of the present application to which an adhesive layer has been applied and cut into a frame shape, and the CCM and electrolyte membrane reinforcing member are attached by heat pressing.

[0066] When the MEA is produced by pressing, a known method (for example, the chemical plating method described in Electrochemical Chemistry, 1985, 53, p.269., or the hot press bonding method of gas diffusion electrodes described in Electrochemical Science and Technology, 1988, 135, 9, p.2209., edited by the Electrochemical Society (J. Electrochem. Soc.)) can be applied. The temperature, tension, and pressure during pressing may be appropriately selected depending on the thickness of the electrolyte membrane, the moisture content, the catalyst layer, and the electrode substrate. Specific pressing methods include roll pressing with a specified pressure and clearance (for example, JP-A-2007-180031) and flat pressing with a specified pressure, and it is preferable to perform the pressing method at a temperature in the range of room temperature to 200° C. from the viewpoints of industrial productivity and suppression of thermal decomposition of polymer materials having ionic groups. The electrolyte membrane reinforcing film of the present invention can be suitably used for applications in which the electrolyte membrane and / or the membrane electrode composite are laminated by roll-to-roll. Here, the temperature during lamination is preferably 80° C. or higher. Furthermore, since the film for reinforcing an electrolyte membrane can improve processing dimensional control particularly when roll pressing is performed, it is more preferable to use the film for this purpose.

[0067] When the electrolyte membrane reinforcing member and the MEA are bonded together by roll pressing, they will inevitably be affected by the transport tension during processing. Therefore, it is believed that setting the thermal shrinkage within the above range will be similarly effective not only for polyarylene sulfide films, but also for polyethylene terephthalate (PET) films, polyethylene naphthalate (PEN) films, polyolefin films, polysulfone films, polyphenylsulfone films, polyethersulfone films, and the like.

[0068] The fuel cell and water electrolysis device of the present invention will now be described. The fuel cell of the present invention has an MEA using the film of the present invention. By using the film of the present invention in the fuel cell, the processing dimensional stability is excellent, leading to a reduction in the yield of stack assembly. The water electrolysis device of the present invention has an MEA using the film of the present invention. By using the film of the present invention in the water electrolysis device, the processing dimensional stability is excellent, which leads to reduction in the yield of stack assembly. EXAMPLES

[0069] [Method of measuring characteristics] (1) 125℃ heat shrinkage rate The film was cut into 10 mm x 150 mm strips with the length in the direction perpendicular to the main alignment axis and the main alignment axis, and a mark was placed at the center 100 mm, and the distance between the marks was measured using the following device (marked distance before heat treatment). Next, a 3 g weight was hung from the film, and the film was heat-treated for 30 minutes in a hot air oven heated to 125°C, and the distance between the marks was measured in the same manner as above (marked distance after heat treatment). The 125°C heat shrinkage was calculated from the obtained marked distance using the following formula. Five samples were measured in both the main alignment axis direction and the direction perpendicular to the main alignment axis, and the average was calculated. Length measuring device: Universal projector Sample size: Length 150mm x width 10mm Heat treatment equipment: Gear oven Heat treatment conditions: 125℃, 30 minutes Load: 3g Calculation method: 125℃ heat shrinkage rate (%) = {(gauge length before heat treatment) - (gauge length after heat treatment)} / gauge length before heat treatment x 100.

[0070] (2) Tearing Measurements were performed using a light-load tear tester (Toyo Seiki Co., Ltd., Type-D) in accordance with JIS K7128 (1998). Measurements were performed 20 times in each of the two directions, the longitudinal direction and the transverse direction, and the average values ​​for each direction were calculated. The test specimens were cut into rectangles 63.5 mm long and 50 mm wide, and a 12.7 mm long cut parallel to the long side was made at the center edge of the short side to serve as the tear initiation point. The ratio of longitudinal to transverse tear strength was calculated from the values ​​in each direction using the following formula. Tear strength ratio = H TD / H MD .

[0071] (3) Surface free energy Four types of liquids were used as the measurement liquids: water, ethylene glycol, formamide, and methylene iodide. A contact angle meter CA-D model manufactured by Kyowa Interface Science Co., Ltd. was used to determine the static contact angle of each liquid with respect to the film surface. The static contact angle was measured 30 seconds after each liquid was dropped onto the film surface. The contact angle obtained for each liquid and each component of the surface tension of the measurement liquid were substituted into the formula below to obtain the simultaneous equation consisting of the following formulas: γ S d ,γ S p ,γ S h I solved it. (γ S d ·γ L d ) 1 / 2 +(γ S p ·γ L p ) 1 / 2 +(γ S h ·γ L h ) 1 / 2 =(1+cosθ) / 2

[0072] Gamma S , γ S d , γ S p , γ S h are the surface free energy, dispersion force component, polar force component, and hydrogen bond component of the film surface, respectively, and γ L , γ L d , γ L p , γ L hLet t represent the surface free energy, dispersion force component, polar force component, and hydrogen bond component of the measured liquid used. Here, the surface tension of each liquid used was the value proposed by Panzer (J. Panzer, J. Colloid Interface Sci., 44, 142 (1973)). In the present invention, the sum of the values ​​of the dispersion force, polar force, and hydrogen bond force components found was taken as the value of the surface free energy.

[0073] (4) Surface roughness (SRa) The average centerline roughness (SRa) was determined under the following conditions using a Surfcorder ET30HK manufactured by Kosaka Laboratory. Stylus curvature radius: 2μm Cutoff: 0.25mm Measurement length: 0.5mm Measurement interval: 5μm Number of measurements: 40.

[0074] (5) Young’s modulus According to JIS K7127 (1999), a tensile test was performed using a tensile tester (RTG-1210 manufactured by A&D Company, Limited) with a sample film having a width of 10 mm set so that the chuck length was 50 mm, at a temperature of 25°C and a tensile speed of 300 mm / min.

[0075] For Young's modulus, the start point of the displacement was set to 0 mm, the end point was set to 10 mm, and the load difference was calculated at a calculation interval of 0.2 mm within the measurement range of displacement from 0 mm to 10 mm. The second, third, and fourth coordinates from the maximum were used as the original data, and the line was linearized using the least squares method, and the slope was taken as the modulus of elasticity. The specimens were cut so that the test length direction was the longitudinal direction and the width direction, and five samples were measured for each, and the average was calculated. Measuring device: A&D Company, Limited / RTG-1210 Sample size: Length 150mm x Width 10mm Chuck length: 50mm Pulling speed: 300mm / min Measurement environment: 25℃ 55% RH or 130℃ Analysis conditions: Displacement mode Start point: 0mm End point: 10mm Pitch: 0.2mm.

[0076] (6) Differential molecular weight distribution (dw / dLog(M)) A differential molecular weight distribution curve is obtained according to JIS K7252 (2016). Specifically, 5 mL of 1-chloronaphthalene (1-CN) is added to 5 mg of sample, and the mixture is gently stirred at 210-220 °C for 20 minutes (visual confirmation of dissolution). Then, filtration is performed using a 0.5 μm filter. Measurement is performed under the conditions shown below to obtain a GPC curve. The obtained GPC curve is converted using a molecular weight calibration curve created by approximating the relationship between the logarithm of the molecular weight of polystyrene and the elution time with a cubic equation to calculate a differential molecular weight distribution curve. Note that the molecular weight is a relative value based on the polystyrene standard, and the differential molecular weight distribution curve can be drawn by plotting the differential molecular weight and its weight fraction, and is normalized so that the peak area is 1. From the obtained differential molecular weight distribution curve, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 4.0 and 5.2 was read.

[0077] Equipment: High temperature GPC equipment (equipment No. GPC-H-2, PL-GPC220 manufactured by Polymer Laboratories) Detector: Refractive index detector (RI) Data interval: Every 0.5 seconds Column: Shodex UT-G (guard column) PLgel 10m MIXED-B-LS (2 pieces) (8.0mm x 30cm, Polymer Laboratories) Solvent: 1-chloronaphthalene Flow rate: 0.7mL / min Column temperature: 210℃ Injection volume: 0.200mL Standard sample: Monodisperse polystyrene manufactured by Tosoh.

[0078] (7) Film thickness The thickness of ten arbitrary points of the polyarylene sulfide film for reinforcing an electrolyte membrane was measured in an atmosphere of 23°C and 65% RH using a contact-type electronic micrometer (K-312A type) manufactured by Anritsu Corp. The arithmetic average value of the thicknesses at the ten points was taken as the film thickness (unit: μm) of the polyarylene sulfide film for reinforcing an electrolyte membrane.

[0079] (8) Processing size control After cutting the film into a size of 110 mm in the longitudinal direction and 30 mm in the transverse direction, mark a 20 mm x 20 mm square in the center of the cut film, making sure that the edges of the film and each side of the mark are parallel.

[0080] Using a high-precision image dimension measuring device (IM-700 manufactured by KEYENCE), measure 20 points in both the lengthwise and widthwise directions on a 20 mm x 20 mm marked line, and the average value in each direction is taken as the dimension before processing in each direction.

[0081] Next, a weight was hung from the center of the short side so that a load of 5 MPa was applied in the longitudinal direction of the film, and the film was heat-treated for 10 minutes in a hot air oven heated to 125°C, and the distance between the opposite sides (longitudinal and transverse directions) of 20 mm x 20 mm was measured in the same manner as above to determine the dimensions after treatment. The dimensional change after processing was calculated using the following formula, and the obtained value was evaluated according to the following criteria. Processing dimensional change (%) = {(dimension before heat treatment) - (dimension after heat treatment)} / dimension before heat treatment x 100 AA: Dimensional change in both the longitudinal direction, width direction, etc. is between -0.2% and 0.2%. A: Dimensional change in both the longitudinal direction, width direction, etc. is between -0.3% and 0.3%. B: Dimensional change in both the longitudinal direction, width direction, etc. is between -0.4% and 0.4%. C: Dimensional change in any direction, such as the length or width, is between -0.4% and 0.4%. D: Dimensional change in both the longitudinal direction, width direction, etc. is less than -0.4% and exceeds 0.4%.

[0082] (9) Flatness After the evaluation of the processing dimension control has been carried out, the sample is visually inspected for deformations such as wrinkles, swells, and distortions of the film. A: Almost no deformation of the film is observed. B: The film has wrinkles and ripples, but is still usable. C: Significant distortion is observed in the film.

[0083] (10) Processability (I) After cutting the film to a size of 110 mm in the longitudinal direction and 30 mm in the transverse direction, soft vinyl chloride sheets (0.5 mm thick, hardness #450) were placed on the top and bottom of the electrolyte membrane reinforcing polyarylene sulfide film, and the center of the cut film was punched out with the soft vinyl chloride sheet to a size of 20 mm x 20 mm using a Thomson blade. At this time, the film edge and each side of the punching were made parallel to each other. Next, a weight was hung from the center of the short side so that a load of 1.5 MPa was applied to the film in the longitudinal direction in terms of the cross-sectional area before punching, and the film was heat-treated for 10 minutes in a hot air oven heated to 125°C, and the periphery of the film opening was observed and judged according to the following criteria. AA: Of the 100 samples tested, none of the films broke due to cracks or fractures, and no cracks or fractures were observed. A: Of the 100 samples tested, none of the films broke due to cracks or breaks, but cracks or breaks were observed in two or less samples. B: Of 100 samples tested, none of the films broke due to cracks or breaks, but cracks or breaks were observed in 4 or fewer samples. C: Of the 100 samples tested, none of the films broke due to cracks or breaks, but cracks or breaks were observed in 6 or fewer samples. D: Of 100 samples tested, 2 or less films were broken due to cracks or breaks. E: Of 100 samples tested, 4 or fewer films were broken due to cracks or breaks. F: Of 100 samples tested, 5 or more films were broken due to cracks or breaks.

[0084] (11) Processability (II) As in the case of processability (I), the film was cut into a size of 110 mm in the longitudinal direction and 30 mm in the transverse direction, and then soft vinyl chloride sheets (0.5 mm thick, hardness #450) were placed on the top and bottom of the electrolyte membrane reinforcing polyarylene sulfide film, and the center of the cut film was punched out with the soft vinyl chloride sheet into a size of 20 mm x 20 mm using a Thomson blade. After that, the state of the punched edge of the frame-shaped edge of each of the four 20 mm sides was observed with a laser microscope. A: Observe 10 samples and the total number of cracks or burrs is 0 to 3 or less. B: Ten samples were observed and the total number of cracks or burrs was 4 or more.

[0085] (Reference Example 1) Preparation of polyphenylene sulfide resin granules (PPS granules) In a 1 kiloliter SUS vessel equipped with a stirrer, 1 kmol of 47% sodium hydrosulfide, 1.02 kmol of 47% sodium hydroxide, 1.6 kmol of N-methyl-2-pyrrolidone (NMP), 0.3 kmol of sodium acetate, and 100 kg of ion-exchanged water were charged, and the mixture was gradually heated to 235°C over about 180 minutes while stirring at 240 rpm and passing nitrogen through at normal pressure. After distilling 209 kg of water and 0.4 kg of NMP, the reaction vessel was cooled to 160°C. In addition, the amount of hydrogen sulfide scattered was 0.02 kmol. To the remaining mixture, 1.02 kmol of p-dichlorobenzene (p-DCB) and 2.40 kmol of NMP were added. The reaction vessel was then sealed under nitrogen gas. The temperature was raised from 160°C to 270°C over 180 minutes while stirring at 400 rpm, and the reaction was carried out at 270°C for 140 minutes. Then, the mixture was cooled from 270°C to 250°C over 15 minutes. At this stage, the amount of water in the system per mole of sulfur component of the charged sulfidizing agent was 1.1 moles. The mixture was then cooled from 250°C to 220°C at an average cooling rate of 0.4°C / min. After reaching 220°C, the mixture was rapidly cooled to near room temperature. The contents were removed, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were filtered off with a sieve (80 mesh). The obtained solid was added with 1 kiloliters of hot water, stirred at 70°C for 30 minutes, and filtered off, three times. The obtained solid was added with 0.3 kilograms of calcium acetate monohydrate and 1 kiloliters of hot water, stirred at 70°C for 30 minutes, and filtered off. The obtained solid was added with 1 kiloliters of hot water, stirred at 70°C for 30 minutes, and filtered off, three times. This was dried under reduced pressure at 120°C for 5 hours to obtain PPS granules.

[0086] (Reference Example 2) Preparation of polyphenylene sulfide resin granules (PPS granules 2) In a 1 kiloliter SUS vessel equipped with a stirrer, 1 kmol of 47% sodium hydrosulfide, 1.02 kmol of 47% sodium hydroxide, 1.6 kmol of N-methyl-2-pyrrolidone (NMP), 0.3 kmol of sodium acetate, and 100 kg of ion-exchanged water were charged, and the mixture was gradually heated to 235°C over about 180 minutes while stirring at 240 rpm and passing nitrogen through at normal pressure. After distilling 209 kg of water and 0.4 kg of NMP, the reaction vessel was cooled to 160°C. In addition, the amount of hydrogen sulfide scattered was 0.02 kmol. To the remaining mixture, 1.02 kmol of p-dichlorobenzene (p-DCB) and 2.40 kmol of NMP were added. The reaction vessel was then sealed under nitrogen gas. The temperature was raised from 160°C to 220°C over 100 minutes while stirring at 400 rpm, and the reaction was carried out at 220°C for 240 minutes. The temperature was then raised from 220°C to 255°C over 60 minutes, 0.8 kmol of water was poured into the system over 10 minutes, and the reaction was continued for 400 minutes. After that, it was cooled from 255°C to 200°C over 100 minutes. After reaching 150°C, it was rapidly cooled to near room temperature using a blower. The contents were removed, 1 kiloliters of NMP was added, and the mixture was stirred at 85°C for 30 minutes, after which the solvent and solids were filtered off with a sieve (80 mesh). 1 kiloliters of NMP was added to the obtained solid, stirred at 85°C for 30 minutes, and filtered off. 1 kiloliters of hot water was added to the obtained solid, stirred at 70°C for 30 minutes, and filtered off, and this operation was repeated three times. 4.5 kilograms of calcium acetate monohydrate and 1 kiloliter of hot water in an aqueous solution were added to the obtained solid, stirred at 70°C for 30 minutes, and filtered off. The obtained solid was added with 1 kiloliter of warm water, stirred at 70° C. for 30 minutes, and filtered. This procedure was repeated twice. This was then dried under reduced pressure at 120° C. for 5 hours to obtain PPS granules 2.

[0087] (Reference Example 3) Preparation of polyphenylene sulfide resin granules (PPS granules 3) PPS granules 3 were obtained in the same manner as in Reference Example 1, except that Reference Example 1 was heated from 160° C. to 270° C. over 120 minutes, the reaction at 270° C. was carried out for 100 minutes, and the amount of low molecular weight components was increased.

[0088] (Reference Example 4) Manufacturing method of PPS pellets (PPS) The PPS granules produced in Reference Examples 1 to 3 were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 310°C, melt-extruded at a residence time of 90 seconds and a screw rotation speed of 160 rpm, extruded in the form of strands, cooled with water at a temperature of 25°C, and immediately cut to prepare chips, obtaining PPS pellets 1 to 3 with a melting point of 280°C.

[0089] (Reference Example 5) Manufacturing method of PPS particle pellets (PPS particles 1) A slurry was prepared by dispersing calcium carbonate particles having an average particle size of 1.0 μm in ethylene glycol at 50% by mass. After filtering the slurry, the slurry was mixed with the PPS granules prepared in Reference Example 1 using a Henschel mixer so that the calcium carbonate content was 8% by mass. The resulting mixture was melt extruded in the same manner as in Reference Example 4 to obtain PPS particle pellets (PPS particles 1) with a particle content of 10% by mass.

[0090] (Reference Example 6) Manufacturing method of PPS particle pellets (PPS particles 2) 8% by mass of spherical silica particles ("Sea Hoster" KE P50, manufactured by Nippon Shokubai Co., Ltd.) having an average particle size of 0.5 μm was mixed with 90% by mass of the PPS granules prepared in Reference Example 1. The resulting mixture was melt extruded in the same manner as in Reference Example 4 to obtain PPS particle pellets (PPS particles 2) having a particle content of 10% by mass.

[0091] Example 1 95 parts by mass of PPS pellet 1 (PPS1) prepared in Reference Example 4 and 5 parts by mass of PPS particle 1 prepared in Reference Example 5 were dry-blended, and then dried under reduced pressure at 180°C for 3 hours. The mixture was then fed to an extruder, melted at a temperature of 310°C under a nitrogen atmosphere, and introduced into a T-die die. The mixture was then extruded into a sheet form from the T-die die to form a molten monolayer sheet, and the molten monolayer sheet was cast onto a cast drum rotating at 4.2 m / min and maintained at a surface temperature of 25°C while being cooled and solidified by an electrostatic application method to obtain an unstretched film. The obtained unstretched film was stretched (MD stretched) at a stretching temperature of 105°C in the longitudinal direction of the film by utilizing the difference in peripheral speed of the rolls. Then, both ends of the film were held by clips, and the film was introduced into a tenter and stretched at a stretching temperature of 103 ° C to a ratio of 3.7 times in the width direction of the film (TD stretching), and heat treatment was performed for 10 seconds with a tenter heated to 266 ° C. Next, the first relaxation treatment (Rx1) was performed with a tenter at 265 ° C with a relaxation rate of 5%, followed by a second relaxation treatment (Rx2) with a tenter at 235 ° C with a relaxation rate of 3%, and after cooling to room temperature, the film edges were removed to obtain a biaxially oriented polyarylene sulfide film with a thickness of 50 μm. Next, the obtained film was annealed for 25 seconds while being transported in an oven heated to 151 ° C so that the tension of the film was 1.1 MPa, and the film was wound up again. After that, in the atmosphere (oxygen concentration 21 volume %), the treatment strength E value = 20 W · min / m 2 The film was subjected to a corona discharge treatment at 400 K to obtain a biaxially oriented polyarylene sulfide film. The physical properties and characteristics of the obtained film are shown in Table 1.

[0092] (Examples 2 to 22) A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the raw materials and / or film-forming conditions were changed to those shown in the table. The physical properties and characteristics of the obtained film are shown in the table.

[0093] (Comparative Examples 1 to 7) A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the film formation conditions were changed to those shown in the table. The physical properties and characteristics of the obtained film are shown in the table.

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097] [Table 4]

[0098] [Table 5]

[0099] [Table 6]

[0100] [Table 7] [Explanation of symbols]

[0101] 1: Polyarylene sulfide film for reinforcing electrolyte membrane 2: Opening

Claims

1. The thermal shrinkage rate (longitudinal S) of a material containing polyarylene sulfide (PAS) resin as the main component when heated at 125° C. for 30 minutes is MD、 Width direction S TD ) in the longitudinal direction S MD is 0.10% or more and 1.20% or less, TD The polyarylene sulfide film for reinforcing an electrolyte membrane has a modulus of -0.50% or more and -0.01% or less.

2. Longitudinal tear strength (H MD ) and tear strength in the transverse direction (H TD 2. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein the polyarylene sulfide film satisfies the following formula: 1.01≦H TD / H MD ≦2.00

3. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein the surface free energy measured on at least one surface of the polyarylene sulfide film is 50 mN / m or more.

4. Thermal shrinkage rate S in the longitudinal direction at 125°C for 30 minutes MD and the thermal shrinkage rate S in the width direction TD 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1 or 2, which satisfies the following formula: -0.85≦5.5S MD +12S TD ≦0.85

5. Heat shrinkage rate (longitudinal S) when heated at 125°C for 30 minutes MD、 Width direction S TD ) in the longitudinal direction S MD is 0.20% or more and 1.00% or less, TD 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein the elastic modulus is −0.40% or more and −0.10% or less.

6. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein the Young's modulus in both the longitudinal direction and the transverse direction is 3.5 GPa or more and 4.5 GPa or less.

7. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein at least one surface of the polyarylene sulfide film has a surface roughness (SRa) of 20 nm or more and 100 nm or less.

8. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein in a molecular weight distribution curve measured by gel permeation chromatography, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 5.2 is 0.10 or more and 0.50 or less. (Measurement method) Obtain the differential molecular weight distribution curve according to JIS K7252 (2016). Specifically, 5 mL of 1-chloronaphthalene (1-CN) is added to 5 mg of sample, and the mixture is gently stirred at 210 to 220° C. for 20 minutes to visually confirm that the sample is dissolved. Then, filtration is performed using a 0.5 μm filter. Measurement is performed under the following conditions to obtain a GPC curve. The obtained GPC curve is converted using a molecular weight calibration curve created by approximating the relationship between the logarithm of the molecular weight of polystyrene and the elution time with a cubic equation to calculate a differential molecular weight distribution curve. Note that the molecular weight is a relative value based on polystyrene, and the differential molecular weight distribution curve is drawn by plotting the differential molecular weight and its weight fraction, and normalized so that the peak area is 1. From the obtained differential molecular weight distribution curve, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 5.2 is read. Equipment: High temperature GPC equipment (equipment No. GPC-H-2, PL-GPC220 manufactured by Polymer Laboratories) Detector: Differential refractive index detector RI Data interval: Every 0.5 seconds Column: Shodex UT-G (guard column) PLgel 10m MIXED-B-LS (2 pieces) (8.0mm x 30cm, manufactured by Polymer Laboratories) Solvent: 1-chloronaphthalene Flow rate: 0.7mL / min Column temperature: 210°C Injection volume: 0.200mL Standard sample: Tosoh monodisperse polystyrene

9. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, wherein in a molecular weight distribution curve measured by gel permeation chromatography, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 4.0 is 0.10 or more and 0.40 or less. (Measurement method) Obtain the differential molecular weight distribution curve according to JIS K7252 (2016). Specifically, 5 mL of 1-chloronaphthalene (1-CN) is added to 5 mg of sample, and the mixture is gently stirred at 210 to 220° C. for 20 minutes to visually confirm that the sample is dissolved. Then, filtration is performed using a 0.5 μm filter. Measurement is performed under the following conditions to obtain a GPC curve. The obtained GPC curve is converted using a molecular weight calibration curve created by approximating the relationship between the logarithm of the molecular weight of polystyrene and the elution time with a cubic equation to calculate a differential molecular weight distribution curve. Note that the molecular weight is a relative value based on polystyrene, and the differential molecular weight distribution curve is drawn by plotting the differential molecular weight and its weight fraction, and normalized so that the peak area is 1. From the obtained differential molecular weight distribution curve, the differential molecular weight distribution value (dw / dLog(M)) when the logarithmic molecular weight Log(M) is 4.0 is read. Equipment: High temperature GPC equipment (equipment No. GPC-H-2, PL-GPC220 manufactured by Polymer Laboratories) Detector: Differential refractive index detector RI Data interval: Every 0.5 seconds Column: Shodex UT-G (guard column) PLgel 10m MIXED-B-LS (2 pieces) (8.0mm x 30cm, manufactured by Polymer Laboratories) Solvent: 1-chloronaphthalene Flow rate: 0.7mL / min Column temperature: 210°C Injection volume: 0.200mL Standard sample: Tosoh monodisperse polystyrene

10. 3. A polyarylene sulfide film roll for reinforcing an electrolyte membrane, comprising the film according to claim 1 or 2 wound up.

11. 3. The polyarylene sulfide film for reinforcing an electrolyte membrane according to claim 1, which is laminated with an electrolyte membrane and / or a membrane electrode assembly in a roll-to-roll manner.

12. A film made of a thermoplastic resin, the heat shrinkage rate (longitudinal S) when heat-treated at a temperature of 125° C. for 30 minutes MD、 Width direction S TD ) in the longitudinal direction S MD is 0.10% or more and 1.20% or less, TD The electrolyte membrane reinforcing film has a resistance to deformation of -0.50% or more and -0.01% or less.

13. An electrolyte membrane reinforcing member using the film according to claim 1 , 2 or 12 .

14. A fuel cell comprising the electrolyte membrane reinforcing member according to claim 13.

15. A water electrolysis device comprising the electrolyte membrane reinforcing member according to claim 13.

Citation Information

Patent Citations

  • Biaxial orientation polyester film for solid polyelectrolyte membrane reinforcement

    JP2007103170A

  • Laminated film for reinforcing solid polymer electrolyte membrane

    JP2013110048A

  • Reinforcement member of solid polymer electrolyte membrane

    JP2016219136A

  • Biaxially oriented polyarylene sulfide film

    WO2021045076A1